The influence of market intelligence and corporate governance on MSME business performance with absorptive capacity as a mediating variable: a case study of Amanda Steamed Brownies, West Java - Pranata Acun Sandriya; Salsa Dila Putri; Zahratunnisa Zahratunnisa; Alfito Deanova (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2026)
This study investigates the role of market intelligence and corporate governance in enhancing the business performance of micro, small, and medium enterprises (MSMEs), with absorptive capacity serving as an intervening variable. The research focuses on a food-sector MSME, Brownies Kukus Amanda, operating in West Java. Data were collected through a structured questionnaire administered to 510 respondents, including business owners, managers, supervisors, and key employees involved in managerial and operational activities. The data were analyzed using Structural Equation Modeling (SEM) with AMOS version 23. The findings reveal that market intelligence has a positive and significant effect on absorptive capacity. Furthermore, absorptive capacity significantly influences both corporate governance and business performance. The results also confirm that absorptive capacity mediates the relationship between market intelligence and business performance. Although corporate governance does not directly affect business performance, it acts as a mediating variable in the relationship between absorptive capacity and business performance. These findings emphasize that improvements in MSME performance largely depend on internal capabilities to absorb, process, and effectively implement market-related information.